복강경 보조 원위부 위절제술의 초기 경험 - 김동일(Dong Il Kim); 김대환(Dae Hwan Kim); 김동헌(Dong Heon Kim); 김광하(Gwang Ha Kim) (Annals of surgical treatment and research, 2008)
Purpose: Recently, laparoscopy assisted gastrectomy has taken its place as one of the main strategies for managing early gastric cancer (EGC). We conducted this study to evaluate its value from the point of view of initial experience. Methods: Between June 2007 and May 2008, 63 patients who underwent laparoscopy assisted distal gastrectomy (LADG, n=43) or open distal gastrectomy (ODG, n=20) for EGC by a single surgeon, enrolled in this retrospective, non-randomized study. The operative procedure was decided on through patients’ preferences. We compared several clicopathological factors and short-term postoperative outcomes between the two groups. Results: There were no significant differences in the patients’ demography and pathologic results between the two groups. The operation time was more shorter (167±23.2 vs. 268±68.6 mins, P＜0.0001) in the ODG group, but the time to first flatus (2.8±0.6 vs. 3.1±0.4 days, P=0.033), the time to first diet (3.0±0.3 vs. 3.6±0.6 days, P＜0.0001), and the duration of hospital stay (9.1±1.2 vs. 11.6±3.1 days, P＜0.0001) were significantly shorter in the LADG group. Although there were no significant differences in postoperative morbidity and mortality between the two groups, one patient died of postoperative myocardiac infarction in the LADG group (P=0.6854). Comparison between before and after learning curve; there were statistically significant differences in the number of retrieved lymph nodes (31.2±13.7 vs. 42.2±13.4, P=0.0185) and the time of operation (295±63.8 vs. 208±30.5 mins, P＜0.0001). Conclusion: Although our results represent initial experiences, we could find some advantages in LADG compared with ODG. We suggest that application of more restrictive indication is required at an earlier time on the learning curve. (J Korean Surg Soc 2008;75:381-387) KCI Citation Count: 0